2016
DOI: 10.1002/ange.201601550
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective, Stereodivergent Hydroazidation and Hydroamination of Allenes Catalyzed by Acyclic Diaminocarbene (ADC) Gold(I) Complexes

Abstract: The gold-catalyzed enantioselective hydroazidation and hydroamination reactions of allenes are presented herein. ADC gold(I) catalysts derived from BINAM were critical for achieving high levels of enantioselectivity in both transformations. The sense of enantioinduction is reversed for the two different nucleophiles, allowing access to both enantiomers of the corresponding allylic amines using the same catalyst enantiomer. Graphical AbstractChiral allylic azides and amines may be obtained by enantioselective h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The trend of utilizing ADCs for enantioselective gold catalysis continued, and another interesting series of H 8 -BINAMderived acyclic diaminocarbenes was revealed by Toste and coworkers in 2016. 162 The modular and convergent synthesis of these ADCs from the corresponding amines and gold isocyanides makes them more appealing chiral ligands. The authors demonstrated the applications of newly developed ligands for gold(I)-catalysed enantioselective hydroazidation and hydroamination reactions of allenes (39a) (Scheme 39).…”
Section: Carbene Ligandsmentioning
confidence: 99%
“…The trend of utilizing ADCs for enantioselective gold catalysis continued, and another interesting series of H 8 -BINAMderived acyclic diaminocarbenes was revealed by Toste and coworkers in 2016. 162 The modular and convergent synthesis of these ADCs from the corresponding amines and gold isocyanides makes them more appealing chiral ligands. The authors demonstrated the applications of newly developed ligands for gold(I)-catalysed enantioselective hydroazidation and hydroamination reactions of allenes (39a) (Scheme 39).…”
Section: Carbene Ligandsmentioning
confidence: 99%
“…17) have shown good catalytic activity for addition reactions to alkenes and alkynes. Selected examples include hydration of ethynylbenzenes, 31 addition of enynes with indoles, 94 hydroazidation and hydroamination of allenes, 98 and hydrosilylation of alkynes. [99][100][101] Most of the addition reactions catalyzed by Au(I) acyclic carbene complexes can be performed at room temperature under mild reaction conditions, while the Pt(II) acyclic carbene complexes work at elevated temperatures of 80-100 1C.…”
Section: Addition Reactionsmentioning
confidence: 99%
“…Similarly, the enantiomeric selectivity of the asymmetric catalytic addition reactions can be enhanced by the introduction of chiral substituents on the acyclic carbene ligands (Table S3, ESI †). 98 Acyclic carbene complexes (Fig. 18) have also been reported to catalyze addition reactions of aldehydes and ketones (Scheme 6).…”
Section: Addition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…82 N-carbamates were also successfully tested by Toste with an enantioselective gold-based catalytic system hydroamination of 1,3-disbustituted allenes. 50 Noteworthy, the team of Breit reported in 2017 the rhodium catalyzed enantioselective hydroamidation of terminal allenes with quinazolones (Scheme 27). 83 The addition of the nucleophile was observed on the-carbon of the allene in the presence of a rhodium/diphosphine system combined with (R)-camphorsulfonic acid.…”
Section: Hydroamidation With Amides Sulfonamides and Carbamatesmentioning
confidence: 99%